Interactive slideshow remote control (SRC) mobile application for android - Mohd Azfar Shazwan, Mustari (2016)
Presentation skills is very important nowadays. Using slideshow as medium to deliver the main point in a presentation is one of the standard used by a presenter. It is widely used in learning, business, and open talk. In order to attract audience, presenter must have a good presentation skills. But presenting by using manual controller such as mouse and keyboard will affect the presentation flows. Presenter need to control their own slideshow yet they need to communicate with the audience. Presenter need to move freely while doing a presentation otherwise the audience will get bored with the presentation or even worse the presenter will lose their attention. Controlling the slideshow without effecting their presentation skill is a very difficult things to do. Based on the observation and research, to solve this problem, presenter need something that they can use to control their slideshow remotely while reducing the interruption with their presentation flows. Developing a mobile application that can control the slideshow with various type of controlling option is the best way to solve this problem. Mobile application is suitable for current daily activity. Because people nowadays used smartphone and bring their smartphone everywhere even at working space. Therefore, mobile application is the best solution to what medium user need to use to control their slideshow remotely. Testing the finished product to a group of target user will help improve any bug or error before it will released as a finished product. It is the best way to identify any problem or improvement by testing the product using the target user. The finished product will help improve the presentation flows of the presenter that used this slideshow remote control. Further improvement of this product will involve in new development of a new mobile application or new version of the current product.